BINARY OPPOSITION AND INTERTEXTUALITY OF CHARACTERS IN THE NOVELS "ALEPH" AND "ALCHEMIST" BY PAULO COELHO - Ruzmatova, Dilnoza; Bebutova, Nargiza (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2025)
This paper presents a comparative analysis of the characters in Paulo Coelho’s novels Aleph and The Alchemist, focusing on the binary opposition and intertextuality between them. Both works reflect Coelho’s spiritual philosophy and explore personal growth through mystical journeys. The protagonists, Paulo and Santiago, are guided by their desire to fulfill their Personal Legends, facing internal conflicts, moral dilemmas, and transformative encounters. The study highlights how each character’s development reflects themes of redemption, faith, and self-realization. The author draws parallels between Coelho’s life and his fictional heroes, underlining autobiographical elements in both novels. Through binary opposition—past vs. present, innocence vs. experience, tradition vs. transformation—the analysis unveils the complexity of human growth and destiny. The concept of intertextuality is applied to examine similarities among major and minor characters, including symbolic figures like Hilal and Fatima, and spiritual guides like J. and Melchizedek. Ultimately, the paper argues that both novels emphasize the value of introspection and perseverance in overcoming life’s trials, as well as the profound impact of love and belief. Coelho’s philosophical message encourages readers to embrace their journey, interpret signs from the universe, and remain faithful to their dreams despite hardships.